RURAL LIFE IN THE USA, AGRICULTURE OF THE USA (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article provides a well-rounded perspective on the multifaceted aspects of rural life and agriculture in the USA. It offers a balanced blend of descriptive narratives and factual information, engaging readers with its detailed portrayal of the agricultural heritage, challenges, innovations, and future prospects in rural America. Its emphasis on sustainability, community resilience, and the cultural significance of agriculture adds depth to the narrative, making it a valuable resource for those interested in understanding the complexities of rural landscapes and the agricultural industry in the United States.